Over-the-Scope Clip Applications as First-Line Therapy in the Treatment of Upper Non-variceal Gastrointestinal Bleeding, Perforations, and Fistulas - Qiu, Jiayu; Xu, Jun; Zhang, Yanxia; Liao, Foqiang; Zhu, Zhenhua; Shu, Xu; Chen, Youxiang; Pan, Xiaolin (Frontiers in Medicine, 2022)
Background: The over-the-scope clip (OTSC) is an innovative device and has been successfully used in endoscopic treatment, however, lack of clinical data from China. The aim of this study is to investigate the OTSC applications in the treatment of upper non-variceal gastrointestinal bleeding (UNVGIB), perforations and fistulas in China. Methods: 80 patients were treated with one OTSC respectively as first-line therapy in our endoscopy center between January 2016 and November 2020. Among them, 41 patients with UNVGIB, 34 patients with perforations and five patients with fistulas. The technical and clinical success rates were used to assess the efficacy of OTSC on above diseases. In addition, we compared the hemostatic efficacy of OTSC with the standard endoscopic therapy in ulcer bleeding and Dieulafoy’s lesion by propensity score match analysis. Results: In general, the OTSC were applied successfully in all patients and achieved 100% (80/80) technical success. The clinical success of all patients was 91.3% (73/80). Among 41 patients with UNVGIB, the clinical success was 85.4% (35/41), for six cases presented with the recurrence. For patients of Dieulafoy’s lesion and under antithrombotic therapy, we found that OTSC treatment both had efficient and reliable hemostasis effect. In addition, according to the characteristics of ulcers, site of bleeding lesion and Blatchford score, all patients received similar and reliable clinical success rates. After propensity score matched, we found that OTSC treatment had low rebleeding rates when compared with standard endoscopic therapy in both Dieulafoy’s lesion (15.0% vs 30.0%) and ulcer bleeding (17.6% vs 29.4%). Among 34 patients with perforations, the clinical success was 100% (34/34). Among five patients with fistulas, one patient failed in maintaining the OTSC before esophageal fistula healing, and achieved the clinical success of 80% (4/5). Conclusion: The OTSC represents a safe and effective endoscopic therapy for UNVGIB, perforations and fistulas. However, OTSC application in some specific lesions or patients are lack of adequate evidence as first-line treatment, such as Dieulafoy’s lesion, ulcer bleeding or the patient under antithrombotic therapy of UNVGIB, etc. Therefore, further more large sample and multi-center clinical trials are required to improve its indications in clinical treatment.